Tarakanova - Roubaud, André (Raymond Bernard, 2012)
The Empress Catherine II is keen to rid herself of the Princess Elisabeth Tarakanova, who has a claim to the throne of Russia. To that end, she sends her devoted Prince Orloff to Venice to seduce her and bring her to St. Petersburg. From the moment they first meet, Orloff and Tarakanova become inseparable, but their love will be the death of them ... [filmsdefrance.com]